Diseases and Decays of Conifers in the Himalayas - Bakshi, B. K. (Indian Forester, 1955)
Diseases of conifers caused by Fomes annosus, Armillaria mellea, Polyporus tomentosus, Fomes pinicola and Fomes robustus have been described. F. annosus and A. mellea are well known among foresters in this country. The other fungi are seldom reported though they are known to cause considerable economic losses to forests in other countries. F. annosus does not attack conifers growing in natural forests or in plantations on suitable sites but becomes parasitic on conifers particularly deodar when the latter is forced in areas unsuitable for its growth. Factors affecting the infection and severity of the disease are discussed. The occurrence, pathology, symptoms and control of the diseases due to all the above five fungi are described. The fungi are described from fruit bodies in nature and also from culture. Decay of conifers due to Lenzites sepiaria, L. striata and L. subferruginea, Poria monticola, P. rixosa, Polyporus schweinitzii and Fomes roseus are described from the point of view of their occurrence, macroscopical and microscopical features of decay in wood, sporophore and cultural characters. Fomes robustus and F. roseus are recorded for the first time in India.